The interface reaction and microstructure control in friction stir lap welding of Al and Ti dissimilar alloys - Z. Zhang; X.Y. Zhang; Y.L. Liu; H.N. Xing (Journal of Materials Research and Technology)
The objective of this study is to investigate the mechanism by which the mechanical properties of Al and Ti dissimilar alloys are controlled during friction stir lap welding (FSLW). To this end, the interfacial reaction is subjected to systematic experimental and numerical analysis. Results indicated that TiAl, Ti3Al, and TiAl3 are coexisting in FSLW of Al/Ti. Ti3Al is generated at Ti side. TiAl3 is generated at Al side. TiAl is generated on the interface. In the formation of the different intermetallic components, the heat-force coupling diffusion takes the key role for the atom diffusions in comparison with the diffusion under purely thermal cycling. The thickness of the interface, specifically the intermetallic layer, is crucial in determining the joint's final tensile strength. However, the ideal thickness of the interface layer is essential for achieving high joint strength in FSLW of Al/Ti. The final strength of the interface can reach 47.25% of the tensile strength of the parent metal (Al).